2016
DOI: 10.1177/0269881116645268
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and attentional bias as predictors of modafinil treatment outcome for retention and drug use in crack-cocaine dependent patients: Results of a randomised controlled trial

Abstract: Baseline impulsivity and attentional bias predicted clinical outcomes in crack-cocaine dependent patients. There were no firm indications that modafinil reduced impulsivity nor attentional bias in this population. Future studies involving cognitive-enhancing medications should include strategies to optimise adherence, to be better able to evaluate their potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 88 publications
3
19
0
1
Order By: Relevance
“…For example, (±)MOD was reported to attenuate craving during cocaine withdrawal and decrease smoked cocaine self-administration in humans (Ballon and Feifel, 2006;Dackis et al, 2005;Hart et al, 2008). However, other studies suggest that (±)MOD is not effective in attenuating impulsivity for cocaine-taking and attentional bias in crack-cocaine-dependent patients (Nuijten et al, 2016). In general, (±)MOD has been reported to have low abuse liability (Mereu et al, 2013), but a rare case of dependence was recently reported when a high dose was given (Krishnan and Chary, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, (±)MOD was reported to attenuate craving during cocaine withdrawal and decrease smoked cocaine self-administration in humans (Ballon and Feifel, 2006;Dackis et al, 2005;Hart et al, 2008). However, other studies suggest that (±)MOD is not effective in attenuating impulsivity for cocaine-taking and attentional bias in crack-cocaine-dependent patients (Nuijten et al, 2016). In general, (±)MOD has been reported to have low abuse liability (Mereu et al, 2013), but a rare case of dependence was recently reported when a high dose was given (Krishnan and Chary, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Human and preclinical evidence demonstrates that other illicit substances are linked with neurocognitive deficits in adolescents and young adults, including cocaine ( Cannizzaro et al, 2014 ; Nuijten et al, 2016 ; Kaag et al, 2016 , Kaag et al, 2014 ; Marhe and Franken, 2014 ; Rose-Jacobs et al, 2011 ; Lundqvist, 2010 ; Meade et al, 2015 ; Fernández-Serrano et al, 2010 ; Sim et al, 2007 ; Rahman and Clarke, 2005 ; Kober et al, 2016 ; Verdejo-Garcia et al, 2015 ; Moreno-López et al, 2015 ; Ide et al, 2014 ; Tau et al, 2014 ; Albein-Urios et al, 2014 ; Ernst et al, 2000 ; Mayer et al, 2013 ), methamphetamine ( Buck and Siegel, 2015 ; Cuzen et al, 2015 ; King et al, 2010 ; Scott et al, 2007 ), MDMA or ecstasy ( Medina et al, 2005 ; Medina and Shear, 2007 ; Costa et al, 2014 ; Price et al, 2014 ; Downey et al, 2015 ; Halpern et al, 2011 ; Scholey et al, 2011 ; McCann et al, 2014 , McCann et al, 2008 ; Jager et al, 2008 ; de Win et al, 2008 ), inhalants ( Takagi et al, 2011a , Takagi et al, 2011b , Takagi et al, 2014 ; Scott and Scott, 2012 , Scott and Scott, 2014 ), heroin ( Zeng et al, 2013 ; Lundqvist, 2010 ; Ornstein et al, 2000 ; Fernández-Serrano et al, 2010 ), cathinones ( Albertson et al, 2016 ; Patrick et al, 2016 ), ketamine ( Chen et al, 2015 ; Nagy et al, 2015 ; Tang et al, 2013 ; Sun et al, 2014 ; Morgan et al, 2012a <...>…”
Section: Background and Rationalementioning
confidence: 99%
“…Cocaine and crack cocaine will be measured in total occasions (max use in mg). Follow-up questions on the TLFB ask about typical route of administration (smoking, oral ingestion, intranasal/snorting, injecting subcutaneous, injecting intramuscular, injecting intravenous), how often they inject cocaine, how often they use clean needles, and how often they smoke it ( Nuijten et al, 2016 ; Conti et al, 2014 ; Novak and Kral, 2011 ). Pictures of various types of cocaine products and typical dosing are provided.…”
Section: Abcd Substance Use Battery: Baseline Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…a major domain of social cognition) and decision-making domains [1518]. These cognitive alterations are associated with lack of adherence to treatment, as well as with higher relapse rates and greater difficulties to adapt to demands of social relationships [1921]. Furthermore, gender represents an additional contributor to differences in clinical outcomes among individuals with CUD [22, 23].…”
Section: Introductionmentioning
confidence: 99%